Factors influencing performance in laparoscopic suturing and knot tying: a cohort study - Armbrust, Lina; Lenz, Moritz; Elrod, Julia; Kiwit, Antonia; Reinshagen, Konrad; Boettcher, Johannes; Boettcher, Michael (European journal of pediatric surgery, 2022)
Background: Laparoscopic suturing and knot tying are regarded as some of the most difficult laparoscopic skills to learn. Training is essential to reach proficiency, but available training opportunities are limited. Various techniques to improve training have been evaluated. It appears that individual-related factors affect initial performance and response to training. Thus, the current study aimed to assess factors influencing laparoscopic-suturing and knot-tying performances. Methods: All patients were trained one-on-one (teacher-student) for 3 hours. Patients were tested before training (bowel anastomosis model) and directly after training (congenital diaphragmatic hernia or esophageal atresia model) to evaluate transferability. Primary endpoints were time, knot quality, precision, knot strength, and overall laparoscopic knotting performance. Moreover, factors such as (1) age, (2) gender, (3) handedness, (4) previous training or operative experience, (5) playing an instrument, (6) sportive activities, and (7) computer gaming which may influence the primary endpoints were assessed. Results: In total, 172 medical students or novice surgical residents were included. Training significantly improved all outcome parameters assessed in the current study. More than 50% of the patients reached proficiency after 3 hours of training. Personal factors like operative experience, playing music instruments, sportive activities, and computer gaming affected some outcome parameters. Handedness and gender affected initial performance but differences partially subsided after training. Younger participants showed a much better response to training. Conclusion: In conclusion, several factors influence initial performance and response to the training of laparoscopic suturing and knot tying. Surgeons who want to improve their laparoscopic performance, should concentrate on playing a musical instrument and performing sports rather than playing videos gaming. It appears that training is a key and more practice opportunities should be incorporated into medical school and surgical curricula. Moreover, handedness may affect the outcome but only if the training concepts are not tailored to the dominant hand of the surgeon. Future training and surgical curricula should adapt to this and tailor their concepts accordingly.